Farmers' Producer Organisations in India: A Critical Examination of Growth, Current Status, and Policy Needs - Malaisamy, A.; Yazhini, A.; Raswanthkrishna M, (Agricultural Sciences: Techniques and Innovations Vol. 1, 2025)
Agriculture plays an important role in India, but it faces various challenges. A large number of farmers in India have small and marginal holdings of less than two hectares, which is linked to the increasing fragmentation of land. Many institutional policies aim to improve farmers’ livelihoods to mitigate the disadvantages of land fragmentation. These measures include the formation of Primary Agricultural Cooperative Society (PACS), Self-Help Group (SHG), Joint Liability Group (JLG) and Common Interest Group (CIG). However, there are limitations to these initiatives, as they often provide considerably more managerial control and influence to a locally powerful individual. Moreover, Indian farmers are proficient producers but face significant challenges in marketing their products due to a lack of access to markets in rural areas, limited awareness of other markets and poor marketing skills to meet demand in accordance with price fluctuations. In response, Farmers Producer Organisations (FPOs) have emerged as pivotal entities aimed at integrating smallholders into mainstream markets. FPOs are collectives of farmers with formal structures and shared goals. The primary aim of FPOs is to diversify high-value crops, help the most disadvantaged people to enhance their access to credit and information services, encourage group efforts and public-private partnerships, open up access to the global market, enable quicker and better prices for produce, and improve supply chain organisation. This paper considered the Scopus database using the Boolean keyword "Farmer" AND "Producer organisation" and identified articles that were shortlisted after screening using the PRISMA framework. While previous studies have offered insights into various aspects of FPOs, there remains a significant lack of cohesive analysis integrating historical trends, current challenges and future policy directions. This study aims to review the efficiency of Farmers Producer Organisations in India, focusing on their evolution, current challenges, and future policy directions.